Hemodynamic shear stress regulates the transcriptional expression of heparan sulfate proteoglycans in human umbilical vein endothelial cell - Liu, J-X; Yan, Z-P; Zhang, Y-Y; Wu, J; Liu, X-H; Zeng, Y (Cellular and Molecular Biology, 2016)
We have previously demonstrated the adaptive remodeling of endothelial glycocalyx under shear stress. However, the underlying mechanism in glycocalyx remodeling, especially the expression of the components heparan sulfate proteoglycans (HSPGs) under shear stress was not completely known. In the present study, we investigated the expression of those HSPGs (syndecan family and glypican-1) in human umbilical vein endothelial cells (HUVECs) responded to the distinct magnitude of shear stress, and performed a systematic and comprehensive analyze on the relationship between shear stress and HSPGs mRNA expression in a temporal manner. During the initial 0.5h of exposure, syndecan-1 mRNA was greatest upregulated by 4 dyn/cm2 of shear stress, and syndecan-4 mRNA was significantly upregulated by 10 dyn/cm2 and 15 dyn/cm2. After 24h of exposure, the greatest increased HSPG mRNA was syndecan-4 under 4 dyn/cm2, and was syndecan-3 under 15 dyn/cm2. The adaptive remodeling of endothelial glycocalyx may due to the change in the expression of those molecules. Furthermore, the changes of those molecules that may associate with the vascular homeostasis and endothelial dysfunction revealed the potential candidate components of the glycocalyx in response to cardiovascular diseases.